UAV based very-high-resolution imaging on Barton Peninsula Antarctica. ... - Park, Hong Lyun; Park, Se-Young; Hyun, Chang-Uk; Kim, Hyun-Cheol; Hong, Soon Gyu; Lee, Ryong (EARSeL Symposium Proceedings, 2014)
UAV (unmanned aerial vehicle) capable of shooting in low-altitude with an advantage of taking a high-resolution is economical and accessible way of obtaining images compared to satellite and conventional aerial photography. In this study, UAV imaging was performed to obtain very-high-resolution images in restrictive environment of Antarctic in Jan 2014. The target area was nearby the King Sejong station located in Barton Peninsula, Antarctica. The UAV was equipped with GPS/INS and IMU, and Canon EOS 5D Mark III camera. Flights considering unexpected weather condition of Antarctica were planned with combination of 22 courses, flight altitude of 100 m, forward overlap of 70% and lateral overlap of 30%. As flight results, about 1,500 images of spatial resolution of about 2 cm were obtained with location and attitude information. In preprocessing steps, brightness adjustment and geometric correction were performed to produce orthoimages. Mosaicked orthoimages was produced with an extent of about 3.1 km2 around ...